Investigating demographic and characteristic of workforce which influence innovation productivity in retail banking in Thailand - leerattanakachorn, GUNN (2016)
The purpose of this paper is to investigate demographic factors and characteristic factors of employee in retail banking in Thailand which affect innovation related behaviour. The study is conducted by using a qualitative research with verbal protocol analysis (VPA) interviewing method. This study is conducted with fourteen participants who are working in retail banking in Thailand. The finding from the research shows the demographic factors of employee which significantly affect innovation related behaviour and creativeness. Firstly, age of employee is related to innovativeness and creativeness. Younger employee is more likely to innovate and generate idea than older employee. Secondly, increasing in organisational tenure negatively affects innovativeness and creativeness of employee. The main reason is increasing in tenure cause employee to stay in comfort zone. Thirdly, there are positive relationship between education level and innovation related behaviour. While, area of study cause differentiation in idea generation. The last demographic factors which significantly affect innovativeness is experience of employee. The professional and non-professional experiences positively impact innovativeness and creativeness. However, gender is not significantly related to innovativeness. Also, the finding shows the common characteristics of employee which affect innovation related behaviour and creativeness. The most common characteristic factors are curiosity, logical thinking, effective communication, and pro-activeness, respectively. The employee who has these characteristic is more likely to participate in innovation activity and are more likely to generate idea. This study provides useful understanding of demographic and characteristic of employee who has potential to innovate and generate idea for organisation. This study could be a benefit to organisation which would use the result as a guideline for recruiting new employee. Also, the organisation can use the results as a guideline to foster and enhance current employee to be more innovative and participate in innovation. However, organisational culture and mechanism are important for building innovative culture. The study only focusses on the individual side. Therefore, the future research would study how culture and mechanism of organisation affect innovation related behaviour of employee. The originality of the study was based on the literatures that focus on the demographic factors and characteristics that affect innovativeness and creativeness.